Facilitator competency rubric in nursing simulations: transcultural adaptation and validation of the German version - Theresa A. Forbrig; Paul Gellert; Maria Biniok; Johannes Gräske (BMC, 2023)
Abstract Background Simulations are part of nursing education. To obtain good results, simulation facilitators need to be competent in simulation pedagogy. Part of this study was the transcultural adaptation and validation of the Facilitator Competency Rubric into German (FCRG) and the evaluation of the factors associated with higher competencies. Method A written-standardized cross-sectional survey was conducted. N = 100 facilitators (mean age: 41.0 (9.8), female: 75.3%) participated. Test-re-test, confirmatory factor analysis (CFA), and ANOVAs were conducted to evaluate the reliability and validity of, and the factors associated with, FCRG. Intraclass correlation coefficient (ICC) values > .9 indicate excellent reliability. Results The FCRG achieved good intra-rater reliability (all ICC > .934). A moderate correlation (Spearman-rho .335, p < .001) with motivation indicates convergent validity. The CFA showed sufficient to good model fits (CFI = .983 and SRMR = .016). Basic simulation pedagogy training is associated with higher competencies (p = .036, b = 17.766). Conclusion The FCRG is a suitable self-assessment tool for evaluating a facilitator's competence in nursing simulation.